Recent advances in 3D-printing-based organ-on-a-chip - Xinkun Wu; Wenwan Shi; Xiaojiang Liu; Zhongze Gu (EngMedicine)
Organ-on-a-chip (OOC) facilitates precise manipulation of fluids in microfluidic chips and simulation of the physiological, chemical, and mechanical characteristics of tissues, thus providing a promising tool for in vitro drug screening and physiological modeling. In recent decades, this technology has advanced rapidly because of the development of various three-dimensional (3D) printing techniques. 3D printing can not only fabricate microfluidic chips using materials such as resins and polydimethylsiloxane but also construct biomimetic tissues using bioinks such as cell-loaded hydrogels. In this review, recent advances in 3D-printing-based OOC are systematically summarized based on materials used for direct or indirect 3D printing of OOC, 3D printing techniques for the construction of OOC, and applications of 3D-printing-based OOC in models of the heart, blood vessels, intestines, liver, and kidney. Moreover, the paper outlines prospective vistas and hurdles within the field, intended to catalyze innovative use of 3D printing methodologies to propel OOC advancements.